2015
DOI: 10.1088/0004-637x/807/1/50
|View full text |Cite
|
Sign up to set email alerts
|

Eight New Milky Way Companions Discovered in First-Year Dark Energy Survey Data

Abstract: We report the discovery of eight new Milky Way companions in~1800 deg 2 of optical imaging data collected during the first year of the Dark Energy Survey (DES). Each system is identified as a statistically significant overdensity of individual stars consistent with the expected isochrone and luminosity function of an old and metal-poor stellar population. The objects span a wide range of absolute magnitudes (M V from -2.2 to -7.4 mag), physical

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
564
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 556 publications
(590 citation statements)
references
References 91 publications
23
564
3
Order By: Relevance
“…This conclusion is supported by deeper imaging data from the Sloan Digital Sky Survey (SDSS, York et al 2000), Pan-STARRS (Kaiser et al 2010), and Dark Energy Survey (DES, Diehl et al 2014), which cover a significant portion of the northern and southern sky and are complete to beyond the host virial radius (i.e. > 300 kpc) at these stellar masses (Tollerud et al 2008;Koposov et al 2008;Laevens et al 2014;Koposov et al 2015;Bechtol et al 2015).…”
Section: Local Group Satellitesmentioning
confidence: 91%
“…This conclusion is supported by deeper imaging data from the Sloan Digital Sky Survey (SDSS, York et al 2000), Pan-STARRS (Kaiser et al 2010), and Dark Energy Survey (DES, Diehl et al 2014), which cover a significant portion of the northern and southern sky and are complete to beyond the host virial radius (i.e. > 300 kpc) at these stellar masses (Tollerud et al 2008;Koposov et al 2008;Laevens et al 2014;Koposov et al 2015;Bechtol et al 2015).…”
Section: Local Group Satellitesmentioning
confidence: 91%
“…This highly speculative suggestion is, however, important in the context of the recently discovered satellite galaxies potentially associated with the Magellanic Clouds (e.g. Bechtol et al 2015;Koposov et al 2015;Martin et al 2015). Figure 9 shows the CMD of NGC 121 including only sources within 3σ of the cluster proper motion (right).…”
Section: Ngc 121mentioning
confidence: 99%
“…The black line gives the result for the 11 classical satellites of the Milky Way, and the black dot is the estimation of Koposov et al (2008), which is based on the estimate of 45 MW satellites with MV < −5 and r < 280kpc from SDSS DR5. Recently more stellites of MW have been discovered by the Dark Energy Survey (DES; Bechtol et al 2015;Drlica-Wagner et al 2015;Koposov et al 2015), the VST-Atlas (Torrealba et al 2016) and Pan-STARRS 3π surveys (Laevens et al 2015a,b). Fig.11 of Bose et al (2017) has included these latest observed satellites, which is consistent with the data shown in our Fig.…”
Section: The Abundance Of Milky Way Satellitesmentioning
confidence: 99%